2018
DOI: 10.15832/ankutbd.446442
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral and Antifungal Activity of Biologically Active Recombinant Bouganin Protein from Bougainvillea spectabilis Willd

Abstract: Bouganin antiviral protein (BAP) gene, one of the ribosome inactivating proteins, isolated from Bougainvillea spectabilis Willd. was cloned, expressed and the antiviral and antifungal activities were investigated. The full-length bouganin antiviral protein gene was amplified by reverse transcription-PCR using mRNA as template extracted from mature leaves. The coding region of bouganin gene was cloned into prokaryotic expression vector pETDuet-1 after amplification with end to end gene specific primers. The rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
1
0
1
Order By: Relevance
“…Salah satu ekstrak nabati yang memiliki potensi untuk dikembangkan bahan aktifnya untuk mengendalikan BCMV atau virus lainnya ialah daun bugenvil. Ekstrak tanaman bugenvil dilaporkan bersifat antiviral karena mengandung gen bouganin antiviral protein (BAP) dengan mekanisme menghambat sintesis protein (Güller et al 2018). Selain ekstrak tanaman, salah satu bahan yang dapat digunakan dalam penurunan tingkat keparahan penyakit adalah kitosan.…”
Section: Pendahuluanunclassified
“…Salah satu ekstrak nabati yang memiliki potensi untuk dikembangkan bahan aktifnya untuk mengendalikan BCMV atau virus lainnya ialah daun bugenvil. Ekstrak tanaman bugenvil dilaporkan bersifat antiviral karena mengandung gen bouganin antiviral protein (BAP) dengan mekanisme menghambat sintesis protein (Güller et al 2018). Selain ekstrak tanaman, salah satu bahan yang dapat digunakan dalam penurunan tingkat keparahan penyakit adalah kitosan.…”
Section: Pendahuluanunclassified
“…Choudhary et al (2008) stated that BBAP1 obtained from Bougainvilea xbuttiana provided high resistance against TMV with N-glycosidase activity. Güller et al, (2018) reported that recombinant bouganin antiviral protein (BAP) from Bougainvillea spectabilis Willd reduced the severity of disease caused by ZYMV. Chen et al (1991) found that 4 micrograms of PAP completely inhibited TMV infection in tobacco plants.…”
Section: Introductionmentioning
confidence: 99%